Tocolytic plant Tectona grandis Linn. extended study on other systemic effect. - Deepali Laxman Jaybhaye; Sushilkumar Varma; Prashant Chaudhary; Vijay Bonde; Amol Gite (Wolters Kluwer Medknow Publications, 2016)
Introduction: Tectona grandis Linn. (T.G) is one of the well-known Indian herbs. In Ayurveda, T.G stem extract has tocolytic effect. Our previous study conformed the tocolytic activity of the T.G stem extract on rat uterine contraction. Conventional tocolytic drugs are known to have cardiovascular, skeletal muscle toxicity. This study is undertaken to observe possible adverse effects of T.G stem extract especially on cardiovascular and musculoskeletal system. Materials and Methods: Wistar rats (Rattus norvegicus) and frogs (Rana tigrina) were used for this study. Animals were divided into six groups. Each group contains six animals. To study the effect on the blood vessels and skeletal muscles, frogs were used and for direct cardiac effects, Wistar rats were used. The results were compared with standard drugs such as sodium nitrate (2%), nifedipine, and magnesium sulfate. Results: After analysis by t-test, it was observed that T.G causes vasodilatation same as that of the sodium nitrate, without causing any cardiac toxicity seen with nifedipine and no neuromuscular blockade as seen with magnesium sulfate. Conclusion: T.G causes uterine tocolytic effect without causing any cardiac toxicity or neuromuscular blockage; however, further human studies are desirable.